2019
DOI: 10.33594/000000018
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Irradiation Inhibits Adipogenic Differentiation and Stimulates Osteogenic Differentiation of Human Tonsil-Derived Mesenchymal Stem Cells: Role of Protein Phosphatase 2B

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Cytosolic Ca 2+ levels were measured using the membrane-permeable Ca 2+ indicator dye Fluo-4 AM (Thermo Fisher Scientific), as described previously [49]. BAECs were pretreated with BAPTA-AM for 1 h before ZEN treatment in the presence of 1 µM Fluo-4 AM.…”
Section: Measurement Of Cytosolic Ca 2+ Levelsmentioning
confidence: 99%
“…Cytosolic Ca 2+ levels were measured using the membrane-permeable Ca 2+ indicator dye Fluo-4 AM (Thermo Fisher Scientific), as described previously [49]. BAECs were pretreated with BAPTA-AM for 1 h before ZEN treatment in the presence of 1 µM Fluo-4 AM.…”
Section: Measurement Of Cytosolic Ca 2+ Levelsmentioning
confidence: 99%
“…The cFIR blanket is simple to use anywhere, as it is autonomous and without a power supply [38][39][40][41][42]. Recent studies suggest that FIR induces nitric oxide [43], a key molecule with an established role in central nervous system function, such that its dysregulation is associated with PD [44].…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that TRPV2 may be involved in placental development [ 30 ]. It has been found that far-infrared radiation inhibits the adipogenic differentiation of tonsil-derived MSCs by inducing intracellular Ca 2+ mobilization [ 83 ]. Further studies have shown that the TRPV2 ion channel acts as a receptor of far-infrared radiation and mediates the inhibition process in the adipogenic differentiation of MSCs [ 84 ].…”
Section: Trp Roles In Stem Cellsmentioning
confidence: 99%